A Legal Analysis of Suspect Designation Based on Investigative Evidence Obtained by the Corruption Eradication Commission (KPK): Analisa Hukum Penetapan Tersangka Yang Didasarkan Alat Bukti Hasil Penyelidikan Oleh KPK - Doni Noviantama; Muhammad Hanif Mahsabihul Ardhi; Wahyu Priyanka Nata Permana (Universitas Islam Indonesia, 2024)
This research is motivated by the practice carried out by the Corruption Eradicating Commission (KPK) in determining someone as a suspect along with the issuance of an Investigation Order and a Notification Letter of Commencement of Investigation. This action raises the suspicion that the initial evidence used to determine a suspect is based on evidence at the investigation stage, not the investigation. From this background, the formulation of the problem arises, namely whether the determination of a suspect based on evidence from the results of an investigation by the KPK can be justified according to law? and what are the legal remedies for determining a suspect based on the results of an investigation by the KPK? This research is a normative legal research with a statutory approach, a case approach and a conceptual approach using secondary data. The data collection technique uses literature studies and legal document studies and the data analysis method uses descriptive-qualitative. The results of the study indicate that the determination of a suspect based on evidence from the results of an investigation is not in accordance with legal provisions, namely the Criminal Procedure Code, the KPK Law, and the Constitutional Court Decision Number: 21/PUU-XII/2014. For the KPK's actions, the legal efforts that can be taken by the suspect are to file a pretrial motion regarding the validity of the suspect's determination to the District Court. The conclusion that can be drawn is that the determination of a suspect based on the results of an investigation is an action that is not in accordance with legal provisions and the legal efforts that can be taken by the suspect are to file a pretrial motion.Keywords: Corruption Eradication Commission, Determination of Suspect, Investigation, Prosecution, Pretrial AbstrakPenelitian ini dilatarbelakangi adanya praktik yang dilakukan oleh KPK dalam menetapkan seseorang sebagai tersangka bersamaan dengan dikeluarkannya Surat Perintah Penyidikan (Sprindik) dan Surat Pemberitahuan Dimulainya Penyelidikan (SPDP). Tindakan tersebut memunculkan dugaan jika bukti permulaan yang digunakan untuk melakukan penetapan tersangka didasarkan pada alat bukti pada tahap penyelidikan bukan penyidikan. Dari latar belakang tersebut memunculkan rumusan masalah yaitu apakah penetapan tersangka yang didasarkan pada alat bukti hasil penyelidikan oleh KPK dapat dibenarkan menurut hukum? dan bagaimana upaya hukum terhadap penetapan tersangka yang didasarkan pada hasil penyelidikan oleh KPK?. Penelitian ini termasuk penelitian hukum normatif dengan pendekatan perundang-undangan, pendekatan kasus dan pendekatan konseptual dengan menggunakan data sekunder. Teknik pengumpulan data menggunakan studi pustaka dan studi dokumen hukum serta metode analisis data menggunakan deskriptif-kualitatif. Hasil penelitian menunjukkan jika penetapan tersangka yang didasarkan pada alat bukti hasil penyelidikan tidak sesuai dengan ketentuan hukum yakni KUHAP, UU KPK, dan Putusan Mahkamah Konstitusi Nomor: 21/PUU-XII/2014. Atas tindakan KPK tersebut, maka upaya hukum yang bisa dilakukan tersangka adalah dengan mengajukan permohonan praperadilan tentang sah tidaknya penetapan tersangka ke Pengadilan Negeri. Kesimpulan yang dapat ditarik adalah penetapan tersangka yang didasarkan pada hasil penyelidikan merupakan tindakan yang tidak sesuai ketentuan hukum dan upaya hukum yang dapat dilakukan tersangka adalah mengajukan permohonan praperadilan.Kata Kunci: Komisi Pemberantasan Korupsi, Penetapan Tersangka, Penyelidikan, Penyidikan, Praperadilan